Journey to PCMA convening leaders 2020 - Chan, Margaret Kit Yok (UiTM Sarawak, 2021)
The Professional Convention Management Association (PCMA) was the organizer ofthe 2020 PCMA Convening Leaders held on the 5-8 January 2020 at the Moscone Center in San Francisco, California. PCMA is the world’s largest, most respected and most recognised network of business events strategists with over 7,000 members and an audience of 50,000 across North America, Europe, the Middle East and Asia. The associationleads the industry forsocial and economic progress, professional and personal development, business growth and organisational success. The annual signature event of PCMA Convening Leaders is the frontrunner ofindustry events that strives for its members to reach higher levels ofprofessional success, deepen personal connections with the business events industry globally, and reach wider audiences for global events and services while supporting local communities through meaningful social impact projects.